Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi di Provinsi Aceh - Muhammad Muhammad; Shinta Liana Putri; Syahrial Pane; Asnidar Asnidar; Ahmad Ridha (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to examine how economic growth in the province of Aceh and the factors that affect economic growth. This study uses quantitative methods, with secondary data obtained from the Central Statistics Agency (BPS) of Aceh Province and (BI) Bank Indonesia. The analysis technique used is multiple data regression using Eviews 10 computer. The time series data in this study reviewed the observation time in a row from 2013 - 2022. The results of this study obtained partially inflation had a negative and insignificant effect on the Economic Growth of Aceh Province, and also partially the Interest Rate had a significant negative effect on the Economic Growth of Aceh Province, and the third factor regarding ZIS partially had a positive and significant effect on the Economic Growth of Aceh Province decreased So it can be stated that simultaneously Inflation, Interest Rates have a significant effect on economic growth. So what states that simultaneously ZIS has a significant effect on Economic Growth in Aceh Province. Partially inflation has a positive and significant effect on economic growth, and interest rates have a positive and significant effect on economic growth, while ZIS has a negative and significant effect on economic growth. Simultaneously inflation, interest rates, and ZIS have a significant effect on economic growth.